The mobile communication antenna structures classification - Hasenko , Anton; Padun , Yurii; Bibik , Mykola (Academic journal Industrial Machine Building Civil Engineering, 2023)
The article analyses the problem of mobile communication antenna structures classification, considers their main design features, advantages and disadvantages. Generalized classification of mobile communication antenna structures operated in Ukraine is proposed. The regular recurrence of accidents and destruction of antenna structures indicate that the existing methods of calculation and design of such structures do not always take into account all their structural features. Technical and constructive solutions, peculiarities of operation of structures under load, aspects of application and their requirements for safe operation are considered, strengths and weaknesses of each type of antenna structures are given. One of the most effective and widely used antenna structures are lattice towers and masts. The main advantage of lattice towers is a small building area, however, from the point of view of consumption, steel masts are more cost-effective with the same height of the structure and payload. However, the cost of building an antenna structure is not always the main criterion for choosing its design scheme. First of all, radio-technical, technological and architectural requirements are of great importance. In the absence of restrictions on geometric parameters, preference is given to towers with a minimum number of faces, for example, when going from a 3-faceted to a 4-faceted tower, its weight increases by 10%. For technical and economic efficiency, not only rational types of cross-sections of elements are selected, but also various combined structural systems are developed. A good example is introduction into mass construction of combined supports on the basis of a conical concrete monopole CK-26, on top of which a steel lattice extension is installed. The structural disadvantage of the combined supports based on the conical concrete monopole CK-26 is their limited bearing capacity at the +2,000...+3,000 m mark, which in a number of cases led to accidental destruction in this particular area.
Keywords: antenna structures; classification; mast; tower; combined support